Self Efficacy Berperan Dalam Penggunaan Metode Kontrasepsi pada Wanita Usia Subur (WUS) Risiko Tinggi - Tarsikah, Tarsikah; Nurvitasari, Rifzi Devi (Malang Journal of Midwifery (MAJORY), 2020)
Use of contraception plays an important role in reducing maternal mortality, especially for high risk fertile age women (FAW), but from several surveys the frequency of use of non-long-term contraceptive methods (non LCM) is still more dominant. Internal factors that play a role in decision-making behavior in the use of contraceptive methods are self efficacy. The purpose of this study was to determine the relationship of self efficacy with the use of contraceptive methods in high risk FAW. Analytic survey research design with cross sectional approach, with a population of 222 respondents, sampling using simple random sampling technique with a sample size of 56 respondents. The research instrument used a questionnaire. Data analysis used Yate’s Correction test. The results showed there was a relationship between self efficacy and the use of contraceptive methods at high risk FAW (p value 0.046), so it was concluded that the higher the self efficacy then FAW would choose the LCM method. Integrated efforts are needed to change the belief that high-risk FAW has a higher risk of complications, so it is necessary to use the non LCM contraception to prepare for a healthy pregnancy. Keywords: Self Efficacy, Contraceptive Methods, High Risk high risk fertile age women